Cr+6 Controlled Nucleation in SiO2-MgO-Al2O3-K2O-B2O3-F Glass Sealant (SOFC) - Garai, Mrinmoy; Karmakar, Basudeb; Roy, Shibayan (Frontiers in Materials, 2020)
This study highlights the strong effect of chromium (Cr6+) as a nucleating agent for SiO2-MgO-Al2O3-B2O3-K2O-F glass sealant. In the process, Al2O3 from the base glass was gradually substituted by K2Cr2O7, which considerably tuned the crystallization characteristics, microstructure, thermal, and mechanical properties. The distinctive feature of this study is the induction of nucleation and crystallization in glass matrix on addition of Cr6+ content performing only annealing heat-treatment (600°C). The melt-quenched SiO2-MgO-Al2O3-B2O3-K2O-F glass with zero Cr6+ content is found amorphous, which in presence of Cr6+ content became crystalline with MgCr2O4, K3CrF6, MgF2, and mullite (3Al2O3.2SiO2) phases. Glassy features in DSC and dilatometric thermal properties (Tg, Td, thermal expansion) were attained in glass without Cr- content, but glass-ceramic-like features obtained for Cr- containing glasses. Large thermal expansion (>11 × 10–6/K) was achieved for such glasses, and that is compatible with the CTE of solid oxide fuel cell (SOFC) components (electrode, interconnect, etc.) at the operating temperature (700–900°C). FESEM study revealed the development of 200–500 nm sized crystallites in 2 mol% K2Cr2O7-containing glass microstructure and that became more compact sorted with 10–50 μm sized crystals in higher Cr-doped glasses. Higher crystallinity was thus ascertained for higher Cr-containing glasses, which influenced the corresponding density and mechanical properties. From nano-indentation measurements, the hardness and Young’s modulus were estimated to be 0.6 (±0.5) and 25 (±10) GPa, respectively, for base glass and in the range of 3.3 to 8.4 and 58 to 94 GPa, respectively, for Cr-containing glass-ceramics. Hardness measured from micro-indentation tests for the base glass was 3.63 (± 0.18) GPa, which increased to 3.94–6.08 GPa for Cr-containing glass-ceramics. Due to the typical microstructure and compatible thermal and mechanical properties, 2 mol% K2Cr2O7-doped SiO2-MgO-Al2O3-B2O3-K2O-F glass can be useable as high temperature sealant (like SOFC).